2020
DOI: 10.1007/s00396-020-04658-9
|View full text |Cite
|
Sign up to set email alerts
|

Diffusive dynamics of elongated particles in active colloidal suspensions of motile algae

Abstract: Swimming microorganisms can influence the diffusion of passive particles. The effect of this swimmer-particle interaction depends on different properties, such as the hydrodynamic field of the swimmer and the relative sizes of microorganisms and particles. We investigated an enhancement of the diffusion of silica doublets in a suspension of microalgae Chlamydomonas reinhardtii in a flat capillary. Depending on the concentration of microswimmers, the translational and rotational diffusion constants increase by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…2016; Ortlieb et al. 2019; von Rüling, Kolley & Eremin 2021), and theoretically, with microswimmers typically being modelled either as force dipoles acting on the surrounding fluid (Pushkin, Shum & Yeomans 2013; Pushkin & Yeomans 2013; Morozov & Marenduzzo 2014; Nordanger, Morozov & Stenhammar 2022), as spherical ‘squirmers’ with an imposed slip velocity along their body (Thiffeault & Childress 2010; Lin et al. 2011; Thiffeault 2015), or as needle-shaped ‘slender swimmers’ with imposed stresses along their body lengths (Saintillan & Shelley 2012; Krishnamurthy & Subramanian 2015).…”
Section: Introductionmentioning
confidence: 99%
“…2016; Ortlieb et al. 2019; von Rüling, Kolley & Eremin 2021), and theoretically, with microswimmers typically being modelled either as force dipoles acting on the surrounding fluid (Pushkin, Shum & Yeomans 2013; Pushkin & Yeomans 2013; Morozov & Marenduzzo 2014; Nordanger, Morozov & Stenhammar 2022), as spherical ‘squirmers’ with an imposed slip velocity along their body (Thiffeault & Childress 2010; Lin et al. 2011; Thiffeault 2015), or as needle-shaped ‘slender swimmers’ with imposed stresses along their body lengths (Saintillan & Shelley 2012; Krishnamurthy & Subramanian 2015).…”
Section: Introductionmentioning
confidence: 99%
“…43,44 All this suggests that active N-MPCD (AN-MPCD) could be very valuable to investigate the dynamics of particles suspended in active media such as colloids and disks in active nematics and particles suspended in swimming bacteria and motile algae. [50][51][52][53] Here we present two MPCD schemes for 3D active nematics. The first one derives from N-MPCD proposed by Shendruk and Yeomans in 2015, in which nematic order arises from an orientation collision operator.…”
Section: Introductionmentioning
confidence: 99%
“…43,44 All this suggests that active N-MPCD (AN-MPCD) could be very valuable to investigate the dynamics of particles suspended in active media such as colloids and disks in active nematics and particles suspended in swimming bacteria and motile algae. 50–53…”
Section: Introductionmentioning
confidence: 99%
“…It also has a more fundamental relevance, as tracers can be used to probe the nature of non-equilibrium fluctuations in active systems, in particular in relation to (equilibrium) Brownian motion [5]. Arguably, the simplest model system for studying tracer diffusion in such "active baths" is a spherical colloidal particle immersed in a dilute suspension of biological microswimmers, such as E. coli [6][7][8][9][10][11][12][13][14][15] or C. reinhardtii [16][17][18][19]. A generic feature of tracer motion in these systems is that the displacement is characterized by ballistic motion at short times (approximately 0.02 − 2 seconds [13]) and diffusive motion at long times, although with a significantly increased translational diffusion coefficient D T compared to the corresponding Brownian one.…”
Section: Introductionmentioning
confidence: 99%
“…Going beyond the case of spherical tracers, a few recent experimental studies have focused on the dynamics of anisotropic passive particles in the form of ellipsoids [14,18] or dumbbells [19] immersed in active suspensions. In addition to the enhanced overall diffusion seen for spherical tracers, these studies found significantly increased rotational diffusion coefficients D R .…”
Section: Introductionmentioning
confidence: 99%